Specific binding of PapI to Lrp-pap DNA complexes. - Kaltenbach, L S (1995)
Expression of pyelonephritis-associated pili (Pap) varies between transcriptionally active (ON) and inactive (OFF) phase states. Pap phase variation is controlled by the binding of leucine-responsive regulatory protein (Lrp) to two pap regulatory DNA regions, each containing a deoxyadenosine methylase site and designated GATC-I and GATC-II. Methylation of these GATC sites modulates binding of Lrp and plays an essential role in phase variation. PapI, an 8.8-kDa pap-encoded regulatory protein, plays a key role in the switch between OFF and ON transcription states. In the absence of PapI, Lrp binds to sites overlapping the papBA promoter and inhibits transcription. Addition of PapI results in a translocation of Lrp binding to sites over 100 bp upstream, resulting in the ON transcription state. Gel shift analysis using radiolabeled PapI shows that PapI binds with high specificity to Lrp-pap DNA complexes but binds only weakly to free Lrp. Protein cross-linking studies indicate that Lrp and PapI directly interact with each other. On the basis of these data, we present a hypothesis in which PapI facilitates the transition between OFF and ON transcription states by binding to Lrp and altering Lrp's affinity for the pap GATC-I and GATC-II regions.